2021
DOI: 10.1080/26395940.2021.1908849
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of high fluoride in water sources and endemic fluorosis in the North-Eastern communities of Gombe State, Nigeria

Abstract: Fluoride content of drinking water sources in 12 communities in North-Eastern states, Nigeria, was investigation. The fluoride concentration analyses were performed using the SPADNS method according to the standard method for examining water and wastewater. Fluoride concentration was in the range of 0.35-3.46 mg/L in the drinking water sources. Notably, communities with high fluoride content above the World Health Organization (WHO) guideline were observed in Tumu-2 (2.88 mg/L), Lapan (3.46 mg/L), Jalingo (1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The dissolution of fluoridebearing minerals and geothermal activities could be the possible source of fluoride in the Precambrian basement parts of the basin. Previous studies in Nigeria such as Akpata et al [80], Giwa et al [81], Malago et al [82], and Waziri et al [83] have suggested that high fluoride concentrations in northeastern and northwestern Nigeria are due to overexploitation of basement and quaternary aquifers. Ingestion of groundwater with high fluoride concentrations could lead to dental and skeletal fluorosis [84,85].…”
Section: Nitrate (Nomentioning
confidence: 99%
“…The dissolution of fluoridebearing minerals and geothermal activities could be the possible source of fluoride in the Precambrian basement parts of the basin. Previous studies in Nigeria such as Akpata et al [80], Giwa et al [81], Malago et al [82], and Waziri et al [83] have suggested that high fluoride concentrations in northeastern and northwestern Nigeria are due to overexploitation of basement and quaternary aquifers. Ingestion of groundwater with high fluoride concentrations could lead to dental and skeletal fluorosis [84,85].…”
Section: Nitrate (Nomentioning
confidence: 99%